ANALISIS PERAWATAN ALAT PEMADAM KEBAKARAN API RINGAN PADA MV. HMT FORTUNE - Galatia Sukoy Salempang Putra; Muhammad Syafril Sunusi; Barnabas Fendy Tallu; Welem Ada (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Fire safety is a critical component of maritime operations, particularly in preventing and controlling onboard fire incidents that may endanger crew, cargo, and vessel integrity. One of the primary tools used during the initial stage of firefighting is the portable fire extinguisher (PFE), although its effectiveness depends heavily on proper maintenance and operational readiness. This study analyzes constraints in PFE maintenance onboard MV. HMT Fortune and evaluates their implications for ship safety, using a qualitative approach through observation and interviews with the Master and Third Officer. The findings show that although PFE availability is adequate, several issues persist, including damaged seals, reduced pressure, outdated inspection labels, poor cleanliness, and improper placement, alongside limited port time, suboptimal documentation, and insufficient crew training. These constraints are categorized into technical, operational, managerial, and human factors. Shipping companies are recommended to strengthen maintenance systems, documentation, and crew training to comply with international safety standards Keywords: Maritime Safety, Portable Fire Extinguishers, Maintenance, Fire Prevention, Vessel Safety